2021
DOI: 10.3389/fmicb.2021.706207
|View full text |Cite
|
Sign up to set email alerts
|

Increased Virulence of Outer Membrane Porin Mutants of Mycobacterium abscessus

Abstract: Chronic pulmonary infections caused by non-tuberculous mycobacteria of the Mycobacterium abscessus complex (MABSC) are emerging as a global health problem and pose a threat to susceptible individuals with structural lung disease such as cystic fibrosis. The molecular mechanisms underlying the pathogenicity and intrinsic resistance of MABSC to antibiotics remain largely unknown. The involvement of Msp-type porins in the virulence and biocide resistance of some rapidly growing non-tuberculous mycobacteria and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…There were two differing events in patients 1S and 2B in the porin locus (corresponding to MAB_1080, MAB_1081) genes. A fusion of the two copies of porin genes was observed in 1S–4 or the short indel observed in isolates 2B–5 through 2B–11 were also found in other publicly available genomes and have been previously described [ 41 ]. In our study, strains harbouring porin mutations (1S–4, 2B–5, 2B–6, 2B–7, 2B–8, 2B–9, 2B–10, and 2B–11) showed markedly reduced porin expression and impaired glucose intake.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…There were two differing events in patients 1S and 2B in the porin locus (corresponding to MAB_1080, MAB_1081) genes. A fusion of the two copies of porin genes was observed in 1S–4 or the short indel observed in isolates 2B–5 through 2B–11 were also found in other publicly available genomes and have been previously described [ 41 ]. In our study, strains harbouring porin mutations (1S–4, 2B–5, 2B–6, 2B–7, 2B–8, 2B–9, 2B–10, and 2B–11) showed markedly reduced porin expression and impaired glucose intake.…”
Section: Discussionsupporting
confidence: 60%
“…Deletion of three (out of four) porin genes mspA , mspC and mspD significantly increased survival of M. smegmatis in J774 macrophages [ 16 ]. Recently de Moura and colleagues [ 41 ] demonstrated that a synthetic allelic replacement of the two porin genes in M. abscessu s subsp. massiliense CIP108297 decreased the growth rate and reduced glucose uptake [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the WGS-data are more comprehensive as these allow the precise identification of novel NTM species from human samples, prediction of genes for virulence, intracellular existence, disease, defense, and toxic compounds of NTM, thus emphasizing other applications of this method (Table 2) [58,121,122]. Moreover, extended datasets of clinical phenotypes and bacterial DNA sequences could resolve ambiguities in the pathogenesis of NTM.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of M. smegmatis porin MspA, MspC, and MspD improves M. smegmatis survival in macrophages, by providing greater resistance of M. smegmatis to host-produced nitric oxide (NO; Fabrino et al, 2009 ). Similarly, deletion of porins mmpA/B in M. abscessus also improves M. abscessus intracellular survival within phagocytic cells and bacterial persistence in SCID mice ( de Moura et al, 2021 ). Porin knockout strain Δ mmpA displays reduced uptake of glucose, but mutants did not display varied uptake by macrophages, susceptibility to NO, or cell cytotoxicity.…”
Section: Non-mycobacteria-specific Virulence Factorsmentioning
confidence: 99%
“…Of note, sequential samples taken from different early and late M. abscessus infections in CF patients show mutations within the mmp porin genes ( Lewin et al, 2021 ). However, phylogenetic analysis by de Moura et al could not establish a contributing role of porin mutations to enhanced virulence or transmission of dominant clinical M. abscessus isolates ( de Moura et al, 2021 ). This suggests that while this class of proteins are significant VFs of other species, porins possessed by mycobacterial species including M. abscessus may perform a role unrelated to virulence.…”
Section: Non-mycobacteria-specific Virulence Factorsmentioning
confidence: 99%